HOW IS THE IMPLEMENTATION OF GOODWILL ACCOUNTING IN INDONESIA? - Askiah, Ummi; Bhaktiningsih, Tri Yuni; Widyana, Sarah; Firmansyah, Amrie (Accounting Study Program, Universitas Ciputra Surabaya, 2025)
Goodwill is generated when one firm merges with another one. When the amount spent on acquiring something is higher than the estimated worth of its assets, it is recorded as goodwill on the financial statement. In the past, goodwill used to be amortized. However, modern procedures now require annual impairment testing, which considers the belief that goodwill has an unlimited life and continued economic value. This study explores the disclosure of goodwill and impairment in technology companies in Indonesia and analyzes the consistency of goodwill impairment reporting under PSAK 48. The study also seeks to understand how technology companies in Indonesia apply accounting standards related to goodwill and its impact on financial statements and company performance. This work employs a qualitative research approach, utilizing data sources from a scoping evaluation of previous research on goodwill. This study demonstrates that the laws regulating goodwill have undergone many revisions, and goodwill is currently recognized as an asset obtained through a corporate merger. It is necessary to assess the impairment of goodwill annually. This research is anticipated to contribute to the existing knowledge on goodwill within financial accounting literature or academic scholarship framework.